2020
DOI: 10.1186/s12882-019-1668-4
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing analysis of intestinal flora changes in ESRD and CKD patients

Abstract: Background: Chronic kidney disease (CKD) disease affects gut flora by causing dysbiosis and lead to systemic inflammatory conditions. Here, we provide intestinal flora changes of CKD patients undertook different hemodialysis therapy. Methods: From 2017 to 2019, a total of 166 patients from Guangzhou Red Cross Hospital were recruited and divided into four groups with 17 cases in healthy control group, 47 cases in CKD non-dialysis group, 49 cases in HD group, and 53 cases in PD group. Intestinal flora genome 16S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…In addition, no significant effect of PD on the gut microbiota of ESRD patients was found in our study. By contrast, Hu et al compared the gut microbiota of PD, HD, non-dialysis CKD and healthy control group, and reported that PD reduced microbial diversity, decreased probiotic butyrate production microbiota, and increased urease -, indole -and p-cresol formation microbiota (Hu J, et al, 2020). The main reason that may explain the difference of results between our study and the study by Hu et al is likely that the differences in the inflammatory state and age of the subjects, which are known to have important influences on the gut microbiota (Borges et al, 2016;Takagi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, no significant effect of PD on the gut microbiota of ESRD patients was found in our study. By contrast, Hu et al compared the gut microbiota of PD, HD, non-dialysis CKD and healthy control group, and reported that PD reduced microbial diversity, decreased probiotic butyrate production microbiota, and increased urease -, indole -and p-cresol formation microbiota (Hu J, et al, 2020). The main reason that may explain the difference of results between our study and the study by Hu et al is likely that the differences in the inflammatory state and age of the subjects, which are known to have important influences on the gut microbiota (Borges et al, 2016;Takagi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Hu et al. compared the gut microbiota of PD, HD, non-dialysis CKD and healthy control group, and reported that PD reduced microbial diversity, decreased probiotic butyrate production microbiota, and increased urease -, indole - and p-cresol formation microbiota ( Hu J, et al., 2020 ). The main reason that may explain the difference of results between our study and the study by Hu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis of the gut microbiome is increasingly recognised to be associated with various medical conditions including chronic kidney disease (CKD) [15][16][17][18]. Vaziri et al demonstrate that CKD was associated with lower diversity and richness of gut microbiota and attributed these to the elevated urea in CKD [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CKD is associated with altered colonic microbiota composition [ 18 , 19 , 20 , 21 ]. Among these changes, increased bacterial families with producers of indole and p-cresol were observed, suggesting a potentially upregulated microbiota in the production of these metabolites [ 19 ].…”
Section: Introductionmentioning
confidence: 99%